Arbitrability of Competition Law Disputes - Kocev, Ljuben (Faculty of Law Iustinianus Primus, 2019)
Throughout the years, the scope of arbitrability has been continuously expanding. There is a growing tendency to consider as arbitrable disputes which in the past fell within the exclusive jurisdiction of national courts. The competence of arbitral tribunals in handling competition law disputes has transpired as one of the most recent global trends, albeit not an entirely uniform one. As a result of the legitimate public interest of states to promote fair market competition and prevent disruptive market actions, competition and antitrust disputes have long been considered to be in the exclusive domain of national courts. Regardless of whether the parties have chosen arbitration as a mechanism for solving dispute which has arisen or might arise, in the past courts were reluctant to allow the parties to bring forth competition disputes to any forum other than state courts. However, through several landmark decisions in the USA and the European Union this rigid stance has been challenged. The main contention is whether, and to what extent can arbitration be considered just as a “switch of venue” and to what extend do arbitrators have the power to decide such disputes. From the arbitrators’ point of view, it is important to assess whether the dispute can be resolved by arbitration i.e. whether the dispute would be arbitrable under the applicable law, and whether the rendered award would be open for challenges and setting aside further down the road. There are situations where public policy dictates dispute to be brought before a national court, but in all other cases an individual assessment needs to be made. Unlike the rest of the world where there is an emerging trend to consider competition law disputes as arbitrable to some extent, in the Republic of North Macedonia there isn’t any guidance as to whether these types of disputes might be submitted to arbitration. As a result, a careful evaluation of the existing laws is required to understand the underlying principles and interests of the stakeholders and assess whether in the current legislation there is a mechanism that would allow for such disputes to be resolved by arbitration. The article aims to examine the possibility of arbitrating antitrust/ competition law disputes. It aims at making an overview of jurisdictions in which there is a tendency to allow such disputes to be resolved by arbitration and through the use of comparative analysis to highlight the differences which exist in those jurisdictions concerning the subject matter which can be subjected to arbitration. It further seeks to evaluate whether the stance taken in other jurisdictions concerning these types of disputes can be reflected within the laws of the Republic of North Macedonia.
Keywords: competition law, antitrust, arbitrability, objective arbitrability, international arbitration